Development of regional folklore book to improve children's literacy - Iis Delviya Octaloca; Asiyah Asiyah; Fatrica Syafri (Atfaluna: Journal of Islamic Early Childhood Education, 2023)
This study aimed to discover the development of the Bengkulu regional storybook in improving students' literacy. The research method used was research within the framework of R&D (Research and Development; research and development with research theory without this test has steps of development research with stages of potential and problems, data collection, product design, product validation, product design revision, product improvement, with the scope of a study carried three validators out first validation at Pagar Dewa, Bengkulu City, second validation at the Tarbiyah and Teacher Training Faculty, as well as the third validation at the Regional Library of Bengkulu City. Based on the results conducted on the development and manufacture of regional folklore storybook product for improving students' literacy, where this product has been validated by experts with a recapitulation of validation results, namely designing experts with a percentage of 96%, story material experts with a rate of 96%, and linguists with a ratio of 96%, with an average validation of 96% with very good criteria, so that the storybook development is feasible to be published and used for children in early age to improve their reading literacy so that the students familiar in Regional Folklore storybook